Lues Maligna in Immunocompetent Individuals: Two Case Reports - Adhikari, Bishnu Prasad; Basnet, Binamra; Neupane, Bidhan; Kumar, Ajay; Sapkota, Surendra; Joshi, Mandeep Dutta; Subedi, Kamala (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Lues maligna, also termed malignant syphilis or rupioid syphilis, is a rare and severe form of secondary syphilis. Clinically, the condition is characterized by unusual nodules and necrotic and ulcerated skin lesions covered by thick, lamellated crusts associated with severe constitutional symptoms. Most of the lues maligna cases have been observed in immunocompromised individuals, including Human Immunodeficiency Virus (HIV) co-infected patients, alcoholics, malnourished individuals, and patients with debilitating illnesses. However, immunocompetent individuals can also develop this form of illness. Herein, we present 2 cases of lues maligna in immunocompetent patients. The first case is a 38-year-old immunocompetent married female, while the second case is a 34-old married male, both presenting with multiple diffuse noduloulcerative lesions with rupioid crusts. Serological tests for syphilis were positive in both patients and a biopsy of both patients showed forms consistent with secondary syphilis.